The city is the classroom: teaching/learning geography from the place - Arruda, Emerson Alves (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
The theoric renewal movement of Geography throughout the 20th century and beginning of the 21st century resulted in criticisms of traditional perspectives of teaching and introduction of new methodological guidelines. Faced with these challenges, the Geography basic education teachers have made efforts to tailor the teaching content to meet the space field experienced by the learner. The present paper aims at contributing to pedagogic practices that could provide the educational use of urban areas in Fortaleza based on Merleau-Ponty’s postulates on perception and corporeity, where the existential context of the learner is the starting point to the understanding of the geographical space. Bearing this principle in mind, we have developed a set of activities at General Murilo Borges Moreira State School. We have contextualized the teaching content to meet the learner’s reality and as a result there was a significant retention of new content.